Don Quixote, Sancho Panza and Dulcinea - Vieira, Maria Augusta da Costa (Estudos Avançados, 2023)
The central purpose of this article is to examine the relationship between the three characters: the knight, the squire and the lady, focusing on Don Quixote. We thereby consider a few episodes to try to understand some of the reasons that make today’s readers (and probably readers from all times) admire and intensely respect a character who, in essence, is a complete madman.